2006
DOI: 10.1007/s10535-006-0092-3
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic electron flow around photosystem 1 is required for adaptation to salt stress in wild soybean species Glycine cyrtoloba ACC547

Abstract: A wild soybean species Glycine cyrtoloba ACC547 was found to possess a high salinity resistance trait. It maintained higher net photosynthetic rate (P N ) and maximal photochemical efficiency (F v /F m ) than the soybean Glycine max cultivar Melrose under salt stress. Saline treatment enlarged the post-illumination transient increase in chlorophyll fluorescence in ACC547 much more than that in Melrose, indicating that its cyclic electron flow around photosystem 1 (CEF1) was accelerated more by salt stress. Add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 24 publications
2
11
0
Order By: Relevance
“…On the contrary, C i values in 600 mmol/l salt-treated plants were significantly higher than those in other treatments when PPFD exceeded 1000 µmol/mol (Figure 3). The high salinity-induced increase of C i values was also observed by Yang et al (2006) and supported the hypothesis that the inhibition of photosynthesis caused by salt accumulation in the mesophyll produces an increase in C i , which reduces the stomatal aperture (Mansfield et al 1990). It was reported that both stomatal and non-stomatal limitations account for a reduction of photosynthesis (Farquhar and Sharkey 1982).…”
Section: Discussionsupporting
confidence: 74%
“…On the contrary, C i values in 600 mmol/l salt-treated plants were significantly higher than those in other treatments when PPFD exceeded 1000 µmol/mol (Figure 3). The high salinity-induced increase of C i values was also observed by Yang et al (2006) and supported the hypothesis that the inhibition of photosynthesis caused by salt accumulation in the mesophyll produces an increase in C i , which reduces the stomatal aperture (Mansfield et al 1990). It was reported that both stomatal and non-stomatal limitations account for a reduction of photosynthesis (Farquhar and Sharkey 1982).…”
Section: Discussionsupporting
confidence: 74%
“…Under stress, free radicals and reactive oxygen species (ROS: O 2 -, OH, H 2 O 2 ) accumulate and damage plant cells (Yang et al 2006;Touchette 2007). To counteract these harmful products, plants produce antioxidants (xanthophylls, peroxidases, and catalases) whose concentrations increase in order to prevent damage from oxidative stress (Noctor andFoyer 1998, Touchette 2007).…”
Section: Discussionmentioning
confidence: 99%
“…ACC547) and Glycine max (cv. Melrose) were germinated and cultivated in Zijingang campus of Zhejiang University as described previously (Yang et al 2006 (Neumann et al 1999) till the sixth leaves grew out. Then all seedlings were divided into two groups: one group was grown continuously in the complete solution as the non-salt stressed control while the other one was grown in complete solution plus 50 mM NaCl as the saltstressed treatment.…”
Section: Methodsmentioning
confidence: 99%
“…Post-irradiation transient in Chl fluorescence was measured using a portable photosynthesis system with an integrating Chl fluorometer (LI-6400-40 leaf chamber fluorometer, LI-COR, USA) according to the procedure described by Yang et al (2006). After dark-adaptation of the sample for 1 h, the minimum (dark) fluorescence yield (F 0 ) was obtained with a weak measuring beam (<0.1 µmol m -2 s -1 ).…”
Section: Methodsmentioning
confidence: 99%